Parenting Homosexual: News Possibilities to be Family - Viana Pottker, Isis Cristine; Baldicera Biazus, Camilla (Revista de Psicologia da IMED, 2013)
Contemporary society has been changing, and with them the family structure was also reorganized, opening new possibilities for interpersonal interaction. The loving choices have also undergone changes and, accordingly, it is natural that homosexual couples also seek satisfaction of their desires family. This work is characterized as a qualitative research that seeks to understand the perceptions and personal motivations of individuals who live opposite the homoparenthood homosexual relationships and the desire to adopt a child. The data collected showed that these individuals have a desire for a family that is also related to the sociocultural aspects. However, the participating subjects show a design that prioritizes family bonding. On this basis, it is concluded that the homoparenthood is a new form can be family, but that requires the attention of a multidisciplinary network to assist and empower these individuals in the construction of parental identity.